A first Holocene leaf wax isotope‐based paleoclimate record from the semi‐humid to semi‐arid south‐eastern Caucasian lowlands. (22nd May 2020) - Bliedtner, Marcel; Zech, Roland; Zech, Jana; Schäfer, Imke; von Suchodoletz, Hans
ABSTRACT: The Holocene paleoclimate of the Caucasus region is rather complex and not yet well understood: while existing studies are mainly based on pollen records from high‐altitude and humid lowland regions, no records are available from the semi‐humid to semi‐arid south‐eastern Caucasian lowlands. Therefore, this study investigated compound‐specific δ 2 H and δ 13 C isotopes of leaf wax biomarkers from Holocene floodplain soils in eastern Georgia. Our results show that the leaf wax δ 2 H signal from the paleosols mostly reflects changes in the moisture source and its isotopic composition. Depleted δ 2 H values before ~8 cal ka bp change towards enriched values after ~5 cal ka bp and become again depleted after ~1.6 cal ka bp. This trend could be caused by Holocene changes of the isotopic compositions of the Black and eastern Mediterranean Sea, and/or by varying contribution of both moisture sources linked with the North Atlantic Oscillation. The leaf wax δ 13 C signal from the paleosols directly indicates varying local water availability and drought stress. Depleted δ 13 C values before ~8 and after ~5 cal ka bp indicate wetter local conditions with higher water availability, whereas more enriched values during the middle Holocene (~8 until at least 5 cal ka bp ) indicate drier conditions with increased drought stress.